Investigation of the Copper Bullion claims, Rua Cove, Knight Island, Alaska - Rutledge, Franklin A.; United States. Bureau of Mines. (Washington, D.C. : U.S. Dept. of the Interior, Bureau of Mines, 1953)
Mode of access: Internet.